2002
DOI: 10.1074/jbc.m201001200
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Keratin K10 in the Basal Layer of the Epidermis Inhibits Cell Proliferation and Prevents Skin Tumorigenesis

Abstract: The inhibition of cell proliferation and Akt and PKC activities was also observed although to a minor extent in low hK10-expressing mice. These animals displayed no overt epidermal phenotype nor overexpression of K10. In these non-phenotypic mice, ectopic K10 expression also resulted in decreased skin tumorigenesis. Collectively, these data demonstrate that keratin K10 in vivo functions include the control of epithelial proliferation in skin epidermis.Keratins are the main components of the intermediate filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 56 publications
7
109
1
1
Order By: Relevance
“…4) might be of a particular relevance. Our recent work has demonstrated that this keratin may impose a cell cycle arrest in keratinocytes in a pRb-dependent manner (Paramio et al, 1999;Paramio et al, 2001a;Santos et al, 2002). Here, we show that K10-expressing cells do not exhibit a proliferative arrest.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…4) might be of a particular relevance. Our recent work has demonstrated that this keratin may impose a cell cycle arrest in keratinocytes in a pRb-dependent manner (Paramio et al, 1999;Paramio et al, 2001a;Santos et al, 2002). Here, we show that K10-expressing cells do not exhibit a proliferative arrest.…”
Section: Discussionmentioning
confidence: 53%
“…Here, we show that K10-expressing cells do not exhibit a proliferative arrest. Given that K10 induces a cell cycle arrest in vivo and suppresses tumor development (Santos et al, 2002), the possible loop between pRb and K10 merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S4). Previous studies showed that reduced Akt activity in TEC was responsible for altered thymic architecture, early involution and defects in keratinocyte proliferation [28][29][30] . In order to determine the implication of Akt in CYR61-mediated TEC proliferation, 2DG-FTOC were cultured with recombinant CYR61 in the presence of Akt inhibitor MK2206.…”
mentioning
confidence: 99%